Restoration of absent in melanoma 2 (AIM2) induces G2/M cell cycle arrest and promotes invasion of colorectal cancer cells - Patsos, Georgios; Germann, Anja; Gebert, Johannes; Dihlmann, Susanne (International journal of cancer, 2010)
Absent in melanoma 2 (AIM2) is a member of the interferon-inducible HIN-200 protein family. Recent findings point to a role of AIM2 function in both inflammation and cancer. In response to foreign cytoplasmic DNA, AIM2 forms an inflammasome, resulting in caspase activation in inflammatory cells. Moreover, AIM2 reduces breast cancer cell proliferation and mammary tumor growth in a mouse model and shows a high frequency of frameshift mutations in microsatellite unstable (MSI-H) gastric, endometrial and colorectal cancers. However, the consequences of AIM2 restoration in AIM2-deficient colon cancer cells have not yet been examined. Using different constructs for expression of AIM2 fusion proteins, we found that AIM2 restoration clearly suppressed cell proliferation and viability in HCT116 cells as well as in cell lines derived from other entities. In contrast to previous reports from breast cancer cells, our cell cycle analyses of colon cancer cells revealed that AIM2-mediated inhibition of cell proliferation is associated with accumulation of cells at late S-phase, resulting in G2/M arrest. The latter correlated well with upregulation of cyclin D3 and p21Waf1/Cip1 as well as with inhibition of cdc2 activity through Tyr-15 phosphorylation. Furthermore, AIM2 restoration affected the adhesion of colorectal cancer cells to fibronectin and stimulated the invasion through extracellular matrix-coated membrane in transwell assays. Consistent with this phenotype, AIM2 induced the expression of invasion-associated genes such as VIM and MCAM, whereas ANXA10 and CDH1 were downregulated. Our data suggest that AIM2 mediates reduction of cell proliferation by cell cycle arrest, thereby conferring an invasive phenotype in colon cancer cells.